Utilization of e-commerce in growing entrepreneur skills on the subject of entrepreneurship - Bambang Triyono (Fakultas Ekonomi dan Bisnis Islam, Institut Agama Islam Negeri (IAIN) Salatiga, 2019)
The aims of this research, first for develop information systems and e-commerce technology as a entrepreneurial study. Second, test try information system and e-commerce technology as entrepreneurial. And the last, knowing intention student after using information systems and e-commerce technology as entrepreneurial study. This study uses research and development method. The population of the study is lecture entrepreneurship and students. The data analysis technique used in this study is Structural Equation Modeling (SEM). The sampling of this study used was the quota. To meet the assumptions of sample adequacy in SEM analysis, the sample size in this study is 125 respondens. The quantitative data collection techniques used is questionnaire with Likert scale and qualitative guide. The findings of the research, it can be concluded that the variable system quality effect the use learning technology. Tools made successfully make students interest to conduct online business about the work that has been made